Watershed drainage analysis by fractal dimension - Spadotto, Anselmo José; Garcia, Luiz Henrique; Barberis, Patricia Lopes; Azevedo, Roberto Bernardo de; Rezende, Marcos Antonio de (Universidade Federal de Minas Gerais, 2000)
The drainage of eight watersheds were analyzed by the frequency of rivers, drainage density and fractal dimension, with the purpose of searching parameters that serve to the watershed management and to the soil use plan. The analyzed soils were Alfisol (typic Rhodustalfs ) and Oxisol (Typic Hapludox). The obtained values of frequency of rivers and drainage density, for the watersheds from 1 to 8, are, respectively: 4.84, 4.91, 5.07, 4.05, 3.84, 2.73, 1.61 and 0.36; and 2.48, 2.59, 3.06, 2.50, 2.10, 1.93, 1.70 and 0.73. For fractal dimension (D) for the watersheds, the obtained values are: 1.21920.0138, 1.22800.0114, 1.25120.0113, 1.22290.0061, 1.23300.0070, 1.18680.0099, 1.24680.0124, 1.28100.0046. The obtained results of the statistical analysis showed that the watershed drainage structure could also be evaluated by fractal dimension, which reflects the soil characteristics; but it is not adequate to discriminate soils of different soil categories, even at the level of soil orders.
Análise da drenagem de bacias hidrográficas por meio da dimensão fractal
Keywords: Drainage; Fractal; Watershed; Drenagem; Fractais; Bacia hidrográfica